2017
DOI: 10.1038/s41598-017-03234-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of GTP cyclohydrolase 1 in cardiomyocytes ameliorates post-infarction cardiac remodeling

Abstract: GTP cyclohydrolase 1 (GCH1) and its product tetrahydrobiopterin play crucial roles in cardiovascular health and disease, yet the exact regulation and role of GCH1 in adverse cardiac remodeling after myocardial infarction are still enigmatic. Here we report that cardiac GCH1 is degraded in remodeled hearts after myocardial infarction, concomitant with increases in the thickness of interventricular septum, interstitial fibrosis, and phosphorylated p38 mitogen-activated protein kinase and decreases in left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
(142 reference statements)
0
13
0
Order By: Relevance
“…The heart was excised, and the left ventricle was homogenized at 4 °C for real-time quantitative reverse transcriptional-polymerase chain reaction analysis of microRNA-21. 26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart was excised, and the left ventricle was homogenized at 4 °C for real-time quantitative reverse transcriptional-polymerase chain reaction analysis of microRNA-21. 26…”
Section: Methodsmentioning
confidence: 99%
“…27 Briefly, non-boiled protein lysate that contained 50 μg of protein was resolved by 6% sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) at 4 °C overnight. 26 Membranes were incubated with a 1:2000 dilution of mouse anti-eNOS monoclonal antibodies (BD Transduction Laboratories, San Jose, CA). The membrane was washed and then incubated with the appropriate anti-mouse secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have showed as cGCH1, which is the rate-limiting enzyme in de novo synthesis of BH4, is down-regulated during adverse cardiac remodeling affecting to cardiac function 6 , 24 , 25 . In 2016 Wu et al, established that cGCH1 could be a potential therapeutic target for treatment of MI in the clinic 6 , as revealed by another study published later in showing that transgenic overexpression of cGCH1 in cardiomyocytes ameliorates cardiac remodeling following MI 26 . These authors also revealed that an transgenic overexpression of cGCH1 protein is related to a lower infarcted size 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2016 Wu et al, established that cGCH1 could be a potential therapeutic target for treatment of MI in the clinic 6 , as revealed by another study published later in showing that transgenic overexpression of cGCH1 in cardiomyocytes ameliorates cardiac remodeling following MI 26 . These authors also revealed that an transgenic overexpression of cGCH1 protein is related to a lower infarcted size 26 . In the current study, we show that cGCH1 expression is decreased in failing hearts and cardiomyocytes under stretching (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also exogenous administration of tetrahydrobiopterin (BH 4 ), an essential cofactor for eNOS function, improved ischemic damage in isolated hearts subjected to I/R [27,29]. Likewise, cardiac-specific overexpression of GTP-cyclohydrolase-1, the rate-limiting enzyme for tetrahydrobiopterin synthesis, improved ischemic preconditioning [12] and also attenuated post-infarction cardiac remodeling [16], most probably by restoration of tetrahydrobiopterin synthesis and thus by the prevention of eNOS uncoupling [10]. Further support of this concept is provided by genetic models, where eNOS knockout mice showed more pronounced ischemic damage, myocardial fibrosis and impaired left-ventricular end-diastolic volume and ejection fraction, when subjected to myocardial infarction [25].…”
mentioning
confidence: 99%